Sliding mode control of direct-drive wave power generation system based on Popov hyperstability theory - XIE Zisen; YANG Junhua; QIU Meng; HUANG Weibang; LIN Huijin (Diance yu yibiao)
Faced with the difficult installation and maintenance of the mechanical speed sensor and hazardous working conditions in wave power generation system, a control strategy combining the speed observer based on the model reference adaptive control and the sliding mode variable structure algorithm is proposed. Taking the voltage and current of the PMLSM as the input, the speed observer is designed based on the adjustable model, the reference model and the speed adaptive law determined by Popov hyperstability theory. By analyzing the hydrodynamic equation of the wave energy conversion device, the expected current at the time of the maximum power capture is obtained, and the sliding mode control algorithm is used to quickly track it. The simulation results show that the proposed speed observer can realize the accurate identification of the speed, and the sliding mode control strategy can accurately track the expected current value. The power optimization effect is obvious, and the system robustness is strong.